Factors associated with US caregivers' uptake of pediatric COVID-19 vaccine by race and ethnicity. Issue 15 (6th April 2023) - Hart, Rebecca J.; Baumer-Mouradian, Shannon; Bone, Jeffrey N; Olson, Prasra; Schroter, Stephanie; Weigert, Rachel M.; Chung, SunHee; Shah, Pareen; Lunoe, Maren M; Evers, Megan; Nelson, Courtney E; Goldman, Ran D; et al.
Highlights: Caregiver acceptance of COVID-19 vaccine for children varies by race/ethnicity. Race/ethnicity did not independently account for differences in vaccine uptake. Factors associated with vaccine uptake differed by race/ethnicity. Caregiver vaccination, PCP, and COVID-19 concerns are important to decision-making. Abstract: Objectives: To assess differences in willingness to vaccinate children against COVID-19, and factors that may be associated with increased acceptance, among US caregivers of various racial and ethnic identities who presented with their child to the Emergency Department (ED) after emergency use authorization of vaccines for children ages 5–11. Study design: A multicenter, cross-sectional survey of caregivers presenting to 11 pediatric EDs in the United States in November-December 2021. Caregivers were asked about their identified race and ethnicity and if they planned to vaccinate their child. We collected demographic data and inquired about caregiver concerns related to COVID-19. We compared responses by race/ethnicity. Multivariable logistic regression models served to determine factors that were independently associated with increased vaccine acceptance overall and among racial/ethnic groups. Results: Among 1916 caregivers responding, 54.67% planned to vaccinate their child against COVID-19. Large differences in acceptance were noted by race/ethnicity, with highest acceptance among Asian caregivers (61.1%) and those who did not specify a listed racial identity (61.1%); caregivers identifying as Black (44.7%) or Multi-racial (44.4%) had lower acceptance rates. Factors associated with intent to vaccinate differed by racial/ethnic group, and included caregiver COVID-19 vaccine receipt (all groups), caregiver concerns about COVID-19 (White caregivers), and having a trusted primary provider (Black caregivers). Conclusions: Caregiver intent to vaccinate children against COVID-19 varied by race/ethnicity, but race/ethnicity did not independently account for these differences. Caregiver COVID-19 vaccination status, concerns about COVID-19, and presence of a trusted primary provider are important in vaccination decisions.